Information seeking and trust on vaccination practices - Olowo, Emmanuel Opeyemi; Hasan, Hamisah; Wirza, Julia (Universiti Putra Malaysia, 2018)
One of the successful health inventions of the 20th century is vaccine that has helped combat and prevent deadly diseases. The eradication of smallpox globally and the elimination of poliomyelitis from the world Health Organization (WHO) regions strongly reflects the success rate of the vaccination programs. However, for some unexplained reasons there were parents of children aged seven years and younger who were hesitant in getting their children vaccinated although these vaccinations may not cost them much. Therefore, it is interesting to examine the factors contributing to such behaviors by these parents. The aim of this paper is to review literature related to the studies on information seeking and trust on vaccination practices. Specifically, the review of literature is aimed at critically assessing past studies that has been conducted on information seeking of vaccination practices.